Analysis of Smash Accuracy in The Game of Badminton Viewed From Arm Muscle Strength And Body Height In PB Athletes Karsa Mandiri Makassar - Andi Taufiq Nur Ilmi; Muh Adnan Hudain; Suwardi; Wahyuddin; Irfan (Indonesian Journal of Physical Activity, 2024)
This study aims to analyze the relationship between arm muscle strength and height with smash accuracy in badminton among PB. Karsa Mandiri Makassar athletes. The research method used is a quantitative approach with a descriptive analysis design, normality, and homogeneity. The research subjects consisted of 16 badminton athletes actively training at PB. Karsa Mandiri Makassar. Data collection was conducted through measurements of arm muscle strength using a dynamometer and height using standard measuring instruments. Smash accuracy was measured through a smash skill test in badminton. The data obtained were analyzed descriptively to describe the characteristics of each variable. Normality tests were conducted to ensure normal data distribution using the Kolmogorov-Smirnov test, while hypothesis testing was conducted using linear regression statistical techniques to see the effect of arm muscle strength and height on smash accuracy. The analysis results showed that the data were normally distributed. Additionally, a positive and significant relationship was found between arm muscle strength and smash accuracy (sig. T = 0.003 < 0.05), as well as between height and smash accuracy (sig. T = 0.019 < 0.05). This indicates that the better the arm muscle strength and the taller the athlete's posture, the better the resulting smash accuracy. The F-test result with a probability value of 0.001 indicates significance below the 0.05 significance level. Therefore, H0 is rejected and H1 is accepted, meaning that the independent variables of arm muscle strength and height simultaneously (together) have an influence on smash accuracy.